2015
DOI: 10.2308/accr-51282
|View full text |Cite
|
Sign up to set email alerts
|

Financial Constraints and Cash Tax Savings

Abstract: We investigate the association between financial constraints and cash savings generated through tax planning. We predict that an increase in financial constraints leads firms to increase internally generated funds via tax planning. We measure financial constraints based on changes in firm-specific and macroeconomic measures. We find that firms facing increases in financial constraints exhibit increases in cash tax planning. Our results indicate that among profitable firms, firm-years with the largest increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
340
3
27

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 492 publications
(398 citation statements)
references
References 38 publications
28
340
3
27
Order By: Relevance
“…By focusing on the impact of corporate tax avoidance on financial constraints, our study differs importantly from the prior literature that investigates how financial constraints affect a firm's tax avoidance behavior (Law and Mills, 2015;Edwards et al, 2016). By focusing on the impact of corporate tax avoidance on financial constraints, our study differs importantly from the prior literature that investigates how financial constraints affect a firm's tax avoidance behavior (Law and Mills, 2015;Edwards et al, 2016).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…By focusing on the impact of corporate tax avoidance on financial constraints, our study differs importantly from the prior literature that investigates how financial constraints affect a firm's tax avoidance behavior (Law and Mills, 2015;Edwards et al, 2016). By focusing on the impact of corporate tax avoidance on financial constraints, our study differs importantly from the prior literature that investigates how financial constraints affect a firm's tax avoidance behavior (Law and Mills, 2015;Edwards et al, 2016).…”
mentioning
confidence: 84%
“…First, by taking an agency perspective, our study complements the recent literature on financial constraints and tax avoidance (Law and Mills, 2015;Edwards et al, 2016) and the role of corporate governance in increasing firm value through tax avoidance (Desai andDharmapala, 2006, 2009;Minnick and Noga, 2010). First, by taking an agency perspective, our study complements the recent literature on financial constraints and tax avoidance (Law and Mills, 2015;Edwards et al, 2016) and the role of corporate governance in increasing firm value through tax avoidance (Desai andDharmapala, 2006, 2009;Minnick and Noga, 2010).…”
mentioning
confidence: 98%
“…Trabalhos mais recentes têm destacado a influência de algumas características da empresa no seu perfil agressividade fiscal, são elas: a qualidade do ambiente informacional da empresa (Gallemore & Labro, 2015); a demora na publicação das demonstrações (Rodrigues, 2017); a predisposição para refazimento de demonstrações financeiras (Ramos, 2017); a eficiência dos mecanismos de controle interno (Martinez, Ribeiro & Funchal, 2015;De Simone, Ege & Stomberg, 2015;Bauer, 2016), a eficiência empresarial na utilização dos recursos (Paste Junior, 2017); as estratégias de negócios e os ciclos de vida das empresas (Higgins, Omer & Phillips, 2015;Silva & Rezende, 2017); as restrições financeiras as quais as empresas estão submetidas (Law & Mills, 2015;Edwards, Schwab & Shevlin, 2016;Da Silva & Martinez, 2017;Richardson, Taylor & Lanis, 2015); as transações com partes relacionas no exterior ; e a utilização dos paraísos fiscais como mecanismo para redução da tributação explícita (Lee, 2017;Dyreng & Lindsey, 2009;Dyreng, Lindsey, Markle & Shackelford, 2015;Taylor & Richardson, 2012). Esses estudos buscam identificar características das firmas que conduzem uma maior ou menor agressividade tributária.…”
Section: Características Das Firmasunclassified
“…Edwards et al (2016) [16] studied the effect of financing constraints on corporate tax avoidance. They pioneered the construction of macro indicators and micro indicators to measure financial constraints.…”
Section: R T Xiementioning
confidence: 99%
“…Edwards et al (2016) [16] examined the impact of financing constraints on corporate tax avoidance and found that the greater the financing constraints the firm faces, the higher its tax avoidance level.…”
Section: Industrial Policy and Corporate Tax Avoidancementioning
confidence: 99%